Abdominal trauma: a report of 129 cases. Issue 571 (May 1973) - Bates, T.
Abstract : A retrospective study of 129 cases of abdominal trauma admitted to a district general hospital over the 8 years 1964-71 is reported. Road traffic accidents accounted for 60% of the cases and had a much higher mortality than domestic or industrial accidents. Laparotomy was carried out in eighty-eight patients, but two patients with a ruptured abdominal viscus died without operation because the diagnosis was not recognized. There were seventy-four cases of renal injury of which thirty-nine were treated conservatively and thirty-four were explored through a laparotomy incision. The indication for urgent operation in every case was the suspicion of an associated intraperitoneal injury and in all but three this was confirmed. Only one injured kidney was explored through the loin after an interval. Nephrectomy was carried out in eight cases (11%). The commonest finding at laparotomy was rupture of the spleen, of which there were fifty-three cases. Major hepatic injuries and rupture of the duodenum carried a very high mortality. In all four cases of retroperitoneal rupture of the duodenum there was a delay in diagnosis of at least 24 hr due to the late onset of physical signs. The overall mortality of patients with proved rupture of an abdominal viscus was 17% but in twenty patients (22%) there was a delay in diagnosis and this group carried a 30% mortality. A diagnostic peritoneal tap was carried out in only fifteen cases, but in nine (60%) gave a false negative result. The place of diagnostic peritoneal lavage in the management of abdominal trauma is discussed.